Lightweight concrete made from crushed oil palm shell: tensile strength and effect of initial curing on compressive strength - Shafigh, P.; Jumaat, Mohd Zamin; Bin Mahmud, H.; Hamid, N.A.A. (Elsevier, 2012)
Oil palm shell (OPS) is a waste lightweight aggregate originating from the palm oil industry, which is approximately 50 lighter than conventional aggregate. In this study, crushed old OPS was used as coarse aggregate. Compressive strength under different curing conditions and the splitting tensile and flexural strengths were compared with those of the normal weight granite concrete. The test results showed that OPS concrete with a compressive strength in the range of 34-53 MPa has a splitting tensile strength range of 2.8-3.5 MPa and flexural strength range of 4.4-7.0 MPa. The sensitivity of compressive strength of OPS concrete in this study is significantly lower than uncrushed OPS concrete reported in the literature. The sensitivity of OPS concrete, under poor curing regime, can be reduced by decreasing the water/cement ratio, increasing the OPS content or reducing the cement content. It was found that there was no substantial difference in 28-day compressive strength for OPS concretes cured initially for 3, 5 and 7 days. The 28-day compressive, splitting tensile and flexural strengths of OPS concrete was found to be 38, 28 and 17, lower than that of granite concrete, respectively.